Crisis Averted: Clinical T1b Renal Mass with Concurrent Arteriovenous Malformation and Renal Vein Thrombus. (17th November 2022) - Zekan, David; Wasef, Kareem; Werner, Zachary; Grammer, Robert; Lombard, Cara; Luchey, Adam; Hajiran, Ali
Abstract : Arteriovenous malformations (AVMs) secondary to renal-cell carcinoma (RCC) are well-described in the literature. Independently, renal vein and inferior vena cava tumor thrombi can be detected in locally-advanced RCC. A 67-year-old gentleman presented with a cT1b renal mass detected on workup for elevated creatinine. Multiphase CT imaging obtained for partial nephrectomy surgical-planning revealed an initially-missed renal cortical AVM. This drastically changed the plan for intervention, including use of an open approach with AVM embolization by interventional radiology prior and avoidance of a nephron-sparing approach. Final pathology confirmed the AVM and a subclinical renal vein thrombus masked by arterial flow on CT imaging, making this the first concurrent case described in the literature. Herein, we describe avoidance of catastrophic intraoperative hemorrhage by careful review of preoperative imaging and provide a literature review of imaging modalities for both renal surgical-planning and detection of tumor thrombi in RCC.